How psychological ownership over nutritional products affects purchase intentions of high-pressure working groups - Liang, Boyu; Yang, Dajun; Tan, Fuqiang; Sun, Dajun; Li, Jianshu (Frontiers in Nutrition, 2024)
This study aims to investigate the influence of psychological ownership of nutritional products on the purchase intention of high-pressure working groups, as well as the underlying mechanisms and boundary conditions of this influence. This study aims to investigate the impact of psychological ownership of nutritional products on the purchase intention of high-pressure working groups, as well as the underlying mechanisms and boundary conditions of this influence. The research contributes through the use of variance analysis, mediation models, and moderation models on data from adult participants over the age of 18, across three experiments.Experiment 1, conducted on the Credamo platform, randomly recruited 285 participants, with 148 males (51.9%) and 137 females (48.1%), and the results indicated a direct impact of psychological ownership on purchase intention. Building upon this, Experiment 2, which also utilized the Credamo platform and recruited 280 participants consisting of 136 males (48.6%) and 144 females (51.4%), further revealed the mediating role of perceived value. Experiment 3, with 265 participants randomly recruited on the Credamo platform, including 131 males (49.4%) and 134 females (50.6%), identified the moderating effect of nutritional awareness.The theoretical contribution of this study lies primarily in its in-depth exploration of the impact of psychological ownership of nutritional products. By integrating the factors of perceived value and nutritional awareness, it provides a systematic explanation for better understanding the purchase intentions of high-pressure working groups.Additionally, this study offers valuable strategies for merchants to enhance the purchase intentions of high-pressure living groups.